2020
DOI: 10.1038/s41598-020-62915-x
|View full text |Cite
|
Sign up to set email alerts
|

Difference in spectral power density of sleep EEG between patients with simple snoring and those with obstructive sleep apnoea

Abstract: Patients with simple snoring (SS) often complain of poor sleep quality despite a normal apnoeahypopnoea index (AHI). We aimed to identify the difference in power spectral density of electroencephalography (EEG) between patients with SS and those with obstructive sleep apnoea (OSA). We compared the absolute power spectral density values of standard EEG frequency bands between the SS (n = 42) and OSA (n = 129) groups during the non-rapid eye movement (NREM) sleep period, after controlling for age and sex. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 46 publications
3
14
0
Order By: Relevance
“…This demonstrates a shift in relative power contribution from the higher frequencies to the lower frequencies, i.e., the delta band, in the severe OSA patients. This is in agreement with previous EEG studies on OSA patients showing an increase in delta power during sleep (38,39) and wakefulness (34). The methodology of computing normalized EEG power, however, allowed this paper to provide a more detailed analysis of the change in the relative importance of each power band, specifically, showing the relatively reduced spectral power in faster frequencies in NREM sleep, which previous studies failed to reveal.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This demonstrates a shift in relative power contribution from the higher frequencies to the lower frequencies, i.e., the delta band, in the severe OSA patients. This is in agreement with previous EEG studies on OSA patients showing an increase in delta power during sleep (38,39) and wakefulness (34). The methodology of computing normalized EEG power, however, allowed this paper to provide a more detailed analysis of the change in the relative importance of each power band, specifically, showing the relatively reduced spectral power in faster frequencies in NREM sleep, which previous studies failed to reveal.…”
Section: Discussionsupporting
confidence: 89%
“…That is, OSA patients who suffered from more severe hypoxia during the night exhibited higher spectral power in the delta frequency band. This is supported by previous studies, which demonstrated an increase in delta spectral power (40,41) and a decrease in beta power (38) in healthy volunteers under hypoxia conditions [see however a mouse study showing contrary results (42)]. In terms of sleep fragmentation, it was found that frontal delta spectral power in NREM sleep was positively correlated with the patients' arousal index and negatively correlated with the proportion of time in N3 sleep.…”
Section: Discussionsupporting
confidence: 81%
“…Other studies have shown that respiration can impact EEG spectral frequencies [ 45 , 46 ]. In this study, caffeine altered respiration for a brief period of time after injection (see Table 1 ), which raises the possibility that EEG changes may result from alterations in respiration.…”
Section: Discussionmentioning
confidence: 99%
“…Reported abnormalities in spectral power analysis involve decreased absolute delta, theta and sigma power and increased beta power during NREM sleep (Ondze et al., 2003). However, inconsistencies are noted, with some reports showing an increased absolute delta activity during NREM sleep (Kang et al., 2020), whereas others show no differences across all frequency bands between OSA subjects and controls for either NREM or REM sleep (Jones et al., 2014). OSA severity also affects sleep microstructure, with increased EEG power across 0.5–32 Hz during REM sleep and an isolated increase in beta power during NREM sleep in men (Appleton et al., 2019).…”
Section: Introductionmentioning
confidence: 99%